Analisis Elasto Plastik Bukaan Silindris Berbasis Hoek-Brown pada Terowongan Kalilingseng - Khalilullah, Hanif; Saptono, Singgih (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
The stability of tunnels excavated within heterogeneous rock masses necessitates analytical approaches capable of realistically representing elasto-plastic behavior. This study evaluates the elasto-plastic response of the Kalilingseng Tunnel (Kulon Progo) employing the Hoek–Brown (H–B) failure criterion and the analytical formulation of Carranza-Torres and Fairhurst (CTF) for cylindrical openings. Rock-mass parameters were derived from field-based classification (GSI = 50) and back-analysis using RocLab, yielding mb = 1.509, s = 0.003866, a = 0.5057, Erm = 1.76 GPa, and ν = 0.28. The in-situ stresses at a depth of 34 m indicate σv = 0.637 MPa, σh = 0.322 MPa, and a normalized stress S0 = 0.0252. Analytical results show an onset of plasticity characterized by a critical internal support pressure Pi* = 0.00213, a relative plastic zone radius ξ = 1.010 (≈1% beyond the excavation boundary), and a nondimensional radial closure Ur = 0.000487, corresponding to an actual displacement ur ≈ 0.73 mm for a tunnel radius b = 1.5 m. The wall-stress profile yields σr(b) = 0.0017 MPa and σθ(b) = 0.958 MPa, both well below the rock-mass strength. The resulting Ground Reaction Curve (GRC) exhibits a smooth, nonlinear decay without any abrupt deformation, consistent with the mild yielding regime described in the nondimensional CTF framework. These findings confirm that the rock mass remains inherently stable, implying that support strategies required for the tunnel are primarily deformation-control measures rather than structural reinforcement.